Results regarding compatibility of some plum cultivars grafted on different rootstocks - M. Butac; B. Zamfirescu; S. Nicolae (Romanian Journal of Horticulture, 2023)
In Romania, the most used plum rootstock, ‘Mirobalan’ does not any problems in terms of graft compatibility and that is why it is widely used. However, it was found that this generative rootstock has low compatibility with the ‘Tuleu gras’ cv. and with all the plum cultivars obtained from it. In this paper, we study the degree of compatibility of 5 plum cultivars (‘Andreea’, ‘Pitestean’, ‘Romanța’, ‘Čačanska Lepotiča’, ‘Jojo’) with 7 Romanian rootstocks (‘Adaptabil’, ‘Mirobolan dwarf’, ‘Mirodad 1’, ‘Mirodad 2’, ‘Redutabil’, ‘BN-4Kr’ and ‘B 83/8’). The evaluation of graft compatibility of these cultivar-rootstock combinations was made through two indices: morphological thickness index of the grafting area (IMÎZA - as a result of the ratio between the surfaces section of the scion, rootstock and grafting union) and anatomical similarity index of the symbionts (IMAAtS) calculated based on the number and diameter of the woody vessels in the scion, rootstock and graft union. Following the measurements, very significant results were obtained, which can explain the degree of affinity between cultivars and rootstocks. The morphological thickness index of the grafting area had values above 0.300, which indicates good and very good graft compatibility in most of the cultivar-rootstock combinations studied, with the exception of the association with ‘Redutabil’ rootstock which have values below 0.300, and the thickness differences between scion, rootstock and graft union were very large, indicating a low level of compatibility between the cultivars studied and this rootstock. The anatomical similarity index of the symbionts had values close to 1, indicating good and very good compatibility. The exception was the combinations of cultivars with the ‘Redutabil’ rootstock, the anatomical similarity index of the symbionts having values below 1